Tailoring geopolymer chemistry for value-added applications - Ye, Kai (Nanyang Technological University, 2024)
From the viewpoint of carbon footprint, geopolymer technology has shown excellent promise as an alternative to traditional ordinary Portland cement (OPC). Additionally, with its ease of manufacturability, inherent fire resistance, chemical stability, durability and compressive strength, the interest in these materials has grown. Despite this, their usage has been narrow. The focus of this thesis is to go beyond the traditional area of using the geopolymer technology to replace OPC, and exploit their potential in value-added applications. The geopolymer concept is demonstrated in applications ranging from fire protective composite panels, transparent interlayer system for fire-resistant glass to durability improvement of deteriorated concrete. This is achieved by systematically understanding the chemistry, tuning the compositions of these silicate systems and exploring how they behave in targeted scenarios.